Factors influencing audit quality in tax audit among IRBM’s tax audit officers in Malaysia - Nurul Fatiha, Sohaimi (2022)
This paper aims to determine the factors that influence audit quality in tax audit among IRBM’s tax audit officers in Malaysia. Inland Revenue Board of Malaysia (IRBM) is a government tax collection agency who collects direct taxes in Malaysia and after the taxpayers implement the Self-Assessment System, their main activity is audit. A tax audit officer is responsible to perform tax audit from one of the three audit units namely Company Audit Unit Other Than Company Audit Unit and Individual Audit Unit. Audit activity is essential as it can be a way to educate taxpayers, hinder non-compliance and increase revenue collections. Hence, it is important to maintain the highest degree of audit quality in tax audit. To achieve that, it is essential to understand factors that could influence audit quality in tax audit in IRBM. Data collection involved 100 tax audit officers of IRBM from three audit units from all over Malaysia. Two theories were applied in this study namely Attribution Theory and Theory of Planned Behaviour. Based on these theories, five factors were identified which are accountability, time limit, job satisfaction, competency, and taxation technical training. Multiple regression analysis was used to examine the relationship between variables. The findings show that accountability, competency, and taxation technical training positively affect audit quality in tax audit, meanwhile, time limit and job satisfaction do not affect audit quality in tax audit.